Selective Serotonin Reuptake Inhibitors and Serotonin–Norepinephrine Reuptake Inhibitors Are Not Associated With Bleeding or Transfusion in Cardiac Surgical Patients. (June 2018) - Smith, Mark M.; Smith, Bradford B.; Lahr, Brian D.; Nuttall, Gregory A.; Mauermann, William J.; Weister, Timothy J.; Dearani, Joseph A.; Barbara, David W.
Abstract : BACKGROUND: Selective serotonin reuptake inhibitor (SSRI) and serotonin–norepinephrine reuptake inhibitor (SNRI) use is known to alter platelet activation and aggregation leading to impairment in hemostasis. Previous studies are ambiguous with regard to bleeding, transfusion, and perioperative complications in patients undergoing cardiac surgery. The purpose of this study was to evaluate the risk of perioperative bleeding, transfusion, morbidity, and mortality in cardiac surgical patients taking SSRI/SNRIs compared with propensity-matched controls. METHODS: Adult patients undergoing cardiac surgery with cardiopulmonary bypass at our institution between January 1, 2004, and December 31, 2014, were eligible for study inclusion. Patients taking SSRI/SNRI medications at the time of surgery were identified and compared against all other patients not taking SSRI/SNRI medications to produce well-matched groups via propensity score analysis. Patients taking SSRI/SNRI medications were matched in a 1:1 ratio to control patients not taking these medications based on an internally estimated propensity score. Primary outcomes included perioperative blood transfusion, chest tube output, and reoperation for bleeding. Secondary outcomes included postoperative complications (renal failure, stroke or transient ischemic accident, prolonged mechanical ventilation, and perioperative myocardial infarction), intensive care unit (ICU) and hospital length of stay (LOS), and 30-day mortality. RESULTS: A total of 1417 pairs of SSRI/SNRI patients and matched controls were retained for analysis. Between SSRI/SNRI patients and matched controls, there was no significant difference in postoperative chest tube output (median, 750.0 vs 750.0 mL; P = .860) or reoperation for bleeding (2.8% vs 2.5%; P = .892). Perioperative transfusion rates across all time points and blood product type were not significantly different between groups, with the overall perioperative transfusion rate for SSRI/SNRI patients 66.5% vs 64.9% for matched controls ( P = .697). Patients in the SSRI/SNRI group had a higher rate of prolonged mechanical ventilation (13.1% vs 8.6%; P = .002), longer ICU LOS (median, 25.5 vs 23.8 hours; P < .001), and longer hospital LOS (median, 6.0 vs 5.0 days; P < .001). Remaining mortality and outcome data were similar between groups. CONCLUSIONS: SSRI/SNRI use was not associated with an increased risk of bleeding or transfusion in patients undergoing cardiac surgery. While there was prolonged mechanical ventilation and increased ICU/hospital LOS in the SSRI/SNRI group, it is unclear that this finding is the result of such medications or rather associated with the underlying psychiatric condition for which they are prescribed. The results of this study suggest that perioperative interruption of SSRI/SNRIs to reduce the risk of perioperative bleeding and transfusion is unwarranted and may risk destabilization of patients' psychiatric condition.